BCG-induced disseminated mycobacterial infection of skin and bone in an otherwise immunocompetent child - Abhishek De; Sumantra Sarkar; Nidhi Sharma; Asad Ansari; Abu Hena Hasanoor Reja; Aarti Sarda (Wolters Kluwer Medknow Publications, 2017)
One 2-year-old undernourished girl presented to our outpatient with large erythematous scaly plaques in arm along with multiple bony swellings over nose, fingers, left foot, and back for the past 1 year. Apart from skin and bone lesions the girl was also had intermittent fever, pallor, irritability, and malnourishment. Her parents gave a history of incomplete healing at the BCG vaccination site. The case was diagnosed to be case of disseminated mycobacterial infection skin and bone with the help of histopathology, radiological examination, and DNA polymerase chain reaction (PCR). DNA PCR from the skin lesion came positive for mycobacteria tuberculosis complex. The girl was treated with 6 months of standard antitubercular drug treatment with very good improvement not only of her cutaneous and bone changes but also of her general health and growth. We report the case because paucity of similar infection in literature and for greater recognition of potential epidemiological threat.